A Model for AI-Based Teaching and Learning Adoption for Elementary School Teachers in West Java, Indonesia - Erlan, Dermawan (2024)
Artificial Intelligence (AI) is a computer system that mimics the human brain's ability to process information and make decisions. AI technology is used to learn patterns in data and make predictions or decisions based on that learning. Based on the current situation, elementary school teachers need help in adopting AI technology due to limited training, lack of resources, and resistance to change. In order to address this problem, this research aims to identify the factors influencing the adoption of AI technology among primary school teachers in West Java, Indonesia. The research involved 384 participants and used a quantitative approach. Specific factors influencing AI adoption were identified by developing a model for AI-based teaching and learning and assessing readiness factors. The results from the study identified optimism, innovativeness, insecurity, discomfort, perceived value, perceived trust, perceived usefulness, and perceived ease of use as factors in the successful adoption of AI among primary school teachers in West Java. The customized adoption model provides a practical roadmap for integrating AI into teaching and learning processes, highlighting regional specificities while remaining relevant to similar educational challenges worldwide. The assessment of readiness factors provides actionable insights for fostering a supportive environment for technology integration. The study concluded with recommendations for future research and implications for educators, administrators, and policymakers.